Post-Ranibizumab injection endophthalmitis in aggressive posterior retinopathy of prematurity - Parijat Chandra; Devesh Kumawat; Ruchir Tewari; Suresh Azimeera (Indian Journal of Ophthalmology, 2019)
A preterm infant with zone 1 aggressive posterior retinopathy of prematurity developed infectious endophthalmitis after intravitreal injection of ranibizumab. Urgent empirical intravitreal therapy with vancomycin, ceftazidime, and dexamethasone along with intravenous therapy with amikacin and meropenem helped in early resolution. Vascularization/activity of disease subsided on follow-up, media cleared, and laser photocoagulation was completed. Later the disease reactivated, developed vitreous membranes and central retinal traction, for which 25-gauge lens-sparing vitrectomy was performed. Emergent treatment helped in salvaging the eye from both aggressive ROP disease and devastating endophthalmitis. Rationale approach to such a case is being discussed.